High arsenic (As) concentrations in the shallow groundwaters of southern Louisiana: Evidence of microbial controls on As mobilization from sediments - Yang, N.; Shen, Z.; Datta, Saugata; Johannesson, K. H. (My University, 2016)
Study region: The Mississippi Delta in southern Louisiana, United States. Study focus: The probable role that microbial respiration plays in As release from the shallow aquifer sediments. New hydrological insights for the region: Shallow groundwaters in southern Louisiana have been reported to contain elevated As concentrations, whereas mechanisms responsible for As release from sediments have rarely been studied in this region. Microbial respiration is generally considered the main mechanism controlling As release in reducing anoxic aquifers such as the shallow aquifers in southern Louisiana and those of the Bengal basin. This study investigates the role microbial respiration plays in As release from shallow aquifer sediments in southern Louisiana through sediment incubation experiments and porewater analysis. Arsenic concentrations were the lowest in the sterilized control experiments, slightly higher in the un-amended experiments, and the highest in the experiments amended with acetate, and especially those amended with both acetate and AQDS (9,10-anthraquinone-2,6-disulfonic acid). Although Fe and Mn generally decreased at the beginning of all the experiments, they did follow a similar trend to As after the decrease. Porewater analysis showed that As and Fe concentrations were generally positively correlated and were higher in the coarse-grained sediments than in the fine-grained sediments. Results of the investigation are consistent with microbial respiration playing a key role in As release from the shallow aquifers sediments in southern Louisiana. © 2015 The Authors.
Citation: Yang, N., Shen, Z., Datta, S., & Johannesson, K. H. (2016). High arsenic (As) concentrations in the shallow groundwaters of southern Louisiana: Evidence of microbial controls on As mobilization from sediments. Journal of Hydrology: Regional Studies, 5, 100-113. doi:10.1016/j.ejrh.2015.11.023
Keywords: Arsenic; Groundwater; Microbial Respiration